Rethinking The United Nations – Nigeria Partnership Towards Girl Child Education and Gender Equality Reforms: A Systematic Review - Anthony Ejue Egberi; Madumelu Harrison Christian Madubueze (Education Policy and Development, 2023)
The study focused on the United Nations-Nigeria cooperation in correcting the skewed male-dominated educational system in the Northern states of Nigeria, characterized by extremist beliefs, inequitable education, and gender inequality. As a result, the report contends that the prevalence of sex discrimination exacerbates concerns about female child education and gender inequality. The paper investigated inequitable quality education (SDGs 4) and gender equality (SDGs 5). Furthermore, the study extracts the UN-Nigeria partnership in transforming the Northern states' male-dominated educational system. It also looked at the factors contributing to inequitable quality education and gender equality and the numerous UN-Nigeria partnerships for girl-child education and gender equality. The study collected data from secondary sources and analyzed the data using content analysis. The paper raised several questions and specifically examined issues such as: why parents in the Northern States believe that girl child education is irrelevant, why all adduction is aimed at girls and the role and challenges of the UN-Nigeria partnership in reforming the male-dominated educational system in the Northern states of Nigeria. Finally, the study concluded with policy recommendations.